Community Emergency Response Team (CERT) Training of High-Risk Teens in the Community of Watts, South Los Angeles, 2013–2014. (11th April 2017) - Ossey, Shamika; Sylvers, Sharon; Oksuzyan, Sona; Smith, Lisa V; Frye, Douglas; Family, Leila; Scott, Jannah; King, Jan B
Abstract: The Community Emergency Response Team (CERT) concept was initially developed for adult members of the community to help prepare for disasters and minimize damage when disasters occur. CERTs also served as a tool for building community capacity and self-sufficiency by supporting a diverse group of people working together in dealing with challenges affecting their communities. The novel approach to CERTs described here sought to involve high-risk youth from low-socioeconomic status communities in CERTs and first aid and cardiopulmonary resuscitation (CPR) training to help them build ties with communities, stay off the streets, and become leaders in the community. It also helped to provide different perspectives on life, while building more resilient communities better prepared to minimize damage when a disaster strikes. After the successful launch of the first high-risk teen CERT cohort in Watts (27 CERT-trained and 14 first aid/CPR-trained), the project was expanded to other community groups and organizations. Seven additional cohorts underwent CERT and first aid/CPR training in 2013 through 2014. This initiative increased CERT visibility within South Los Angeles. New partnerships were developed between governmental, nongovernmental, and community-based organizations and groups. This model can be used to expand CERT programs to other communities and organizations by involving high-risk teens or other high-risk groups in CERT training. ( Disaster Med Public Health Preparedness . 2017;11:605–609)